2016
DOI: 10.1017/s1368980016001981
|View full text |Cite
|
Sign up to set email alerts
|

Brazilians’ experiences with iron fortification: evidence of effectiveness for reducing inadequate iron intakes with fortified flour policy

Abstract: Objective: To assess Fe intake, calculate the prevalence of inadequate Fe intake and identify food contributors to Fe intake during 2003 and 2008 in a populationbased study, reflecting before and after the mandatory fortification of flour with Fe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
2
10
0
2
Order By: Relevance
“…However, iron deficiency is the most common cause of anemia ( World Health Organization, 2015 ). Iron-deficiency anemia interventions have centered primarily on nutrition-specific approaches (e.g., dietary or micronutrient supplementation ( Galloway et al, 2002 ; Vieira et al, 2017 )), targeting the most proximate determinants of the problem ( Bhutta et al, 2013 ). Much attention has also been given to fortification of cereals and other food crops, for example, production of iron-rich beans and pearl millet ( Haas et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, iron deficiency is the most common cause of anemia ( World Health Organization, 2015 ). Iron-deficiency anemia interventions have centered primarily on nutrition-specific approaches (e.g., dietary or micronutrient supplementation ( Galloway et al, 2002 ; Vieira et al, 2017 )), targeting the most proximate determinants of the problem ( Bhutta et al, 2013 ). Much attention has also been given to fortification of cereals and other food crops, for example, production of iron-rich beans and pearl millet ( Haas et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient intake recommendations, such as those from Dietary Reference Intakes, are used worldwide for several purposes in the nutrition field, especially for dietary planning and assessment [1], food guide development [2], and fortification and nutrition-related policies [3]. Studies from developed [4,5] and developing countries [6] have shown a high prevalence of inadequate intakes of some nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…The mandatory fortification of wheat flour with iron and folic acid in Brazil may be one possible explanation for the lower iron intake in the post-modeled estimations, since whole wheat flour is not enriched (BRASIL, 2017). Consistent with this, bread (including all types of bread) was among the main contributors to iron intake in post-fortification period among São Paulo residents (VIEIRA et al, 2017). In this sense, findings support the balance between refined and whole grains, but raises questions whether the replacement should be done to all grain foods consumed (JONES; GARCÍA; BRAUN, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…In this sense, findings support the balance between refined and whole grains, but raises questions whether the replacement should be done to all grain foods consumed (JONES; GARCÍA; BRAUN, 2019). On the other hand, the Brazilian diet comprises other iron food sources, such as beans and meat, that along with vegetables, were the main contributors to iron intake in the pre-fortification period (SOUZA et al, 2013;VIEIRA et al, 2017). In this sense, dietary strategies aiming at improving nutritional quality of grain foods consumed by the population must be combined with simultaneous actions to improve diet quality, such as increase fruits and lower sodium intake (OTTO et al, 2016;GBD…, 2019).…”
Section: Discussionmentioning
confidence: 99%